Expanding the PET radioisotope universe utilizing solid targets on small medical cyclotrons. Issue 49 (21st September 2021) - George, K. J. H.; Borjian, S.; Cross, M. C.; Hicks, J. W.; Schaffer, P.; Kovacs, M. S.
Abstract : The production of novel radioisotopes on small-to-medium cyclotrons equipped with solid targets will be vital to meet the demand of theragnostics research. Abstract : Molecular imaging with medical radioisotopes enables the minimally-invasive monitoring of aberrant biochemical, cellular and tissue-level processes in living subjects. The approach requires the administration of radiotracers composed of radioisotopes attached to bioactive molecules, the pairing of which considers several aspects of the radioisotope in addition to the biological behavior of the targeting molecule to which it is attached. With the advent of modern cellular and biochemical techniques, there has been a virtual explosion in potential disease recognition antigens as well as targeting moieties, which has subsequently opened new applications for a host of emerging radioisotopes with well-matched properties. Additionally, the global radioisotope production landscape has changed rapidly, with reactor-based production and its long-defined, large-scale centralized manufacturing and distribution paradigm shifting to include the manufacture and distribution of many radioisotopes via a worldwide fleet of cyclotrons now in operation. Cyclotron-based radioisotope production has become more prevalent given the commercial availability of instruments, coupled with the introduction of new target hardware, process automation and target manufacturing methods. These advances enable sustained, higher-power irradiation of solid targets that allow hospital-based radiopharmacies to produce a suite of radioisotopes that drive research, clinical trials, and ultimately clinical care. Over the years, several different radioisotopes have been investigated and/or selected for radiolabeling due to favorable decay characteristics ( i.e. a suitable half-life, high probability of positron decay, etc. ), well-elucidated chemistry, and a feasible production framework. However, longer-lived radioisotopes have surged in popularity given recent regulatory approvals and incorporation of radiopharmaceuticals into patient management within the medical community. This review focuses on the applications, nuclear properties, and production and purification methods for some of the most frequently used/emerging positron-emitting, solid-target-produced radioisotopes that can be manufactured using small-to-medium size cyclotrons (≤24 MeV).